Perdido en el paraíso - Nooteboom, Cees, 1933- (Nuevos tiempos (Madrid, Spain), 2014)
Alma, a young Brazilian women recovering from a traumatic and brutal attack, sets out from Sao Paulo and winds up in Australia, where Dutch novelist Erik Zontag, in Perth for a literary conference, stumbles upon a winged woman curled up in a closet in an empty house.